PERMUDAAN ALAMI DALAM HUTAN BEKAS TEBANGAN DI SEKUNDUR, SUMATRA UTARA - Mirmanto, Edi (Jurnal Teknologi Lingkungan, 2009)
A phytososiological analysis of saplings was made using quadrate method in the six yearsold logged-over forest at Sekundur, North Sumatra. The results showed that within 0.2hectare plot, 123 species belonging to 79 genera and 36 families were recorded. Threecommunity types were recognized, i.e. Agrostistachys longifolia - Teijsmanniodendronsarawakanum, Macaranga hypoleuca - Macaranga pruinosa and Endospermummalaccensis - Macaranga javanica communities. The structure and floristic compositionof each community varies and they were related primarily with the forest disturÃ‚Â¬bance.There were found that the number of both species and individuals of sapling decreasedwith increasing of the forest disturbance